Clinical case of funicular myelosis in combination with a concomitant genetic predisposition to folate cycle disorder - Shulga , O.D.; Popko, E.A.; Chabanova , A.S.; Kotsiuba , O.G.; Hussain, Q. (Medicni Perspektivi, 2024)
Funicular myelosis (subacute combined degeneration) is a disease characterized by the development of degeneration of the posterior and lateral cords of the spinal cord. Funicular myelosis is a neurological complication of vitamin B12 deficiency, which occurs as a result of reduced intake of vitamin B12 with food, malabsorption, in connection with taking some drugs (metformin, proton pump inhibitors, and nitrous oxide), with invasion by Diphyllobothrium latum. The disease is usually characterized by the presence of paresthesias, the development of sensitive ataxia, and impaired gait. The aim of the work was to demonstrate a clinical case of funicular myelosis in a young patient in order to improve the diagnostic process, paying attention to the genetic profile and identifying a concomitant predisposition to folate cycle disorder. A clinical case of funicular myelosis in a 39-year-old woman is described. The patient came to the neurology department with complaints of numbness in the upper and lower limbs, periodic shooting pains along the spine when the head is tilted forward. During the neurological examination, the following was observed: a decrease in vibrational, muscle-joint, discrimination sensitivity in the upper limbs, paresthesias in the distal parts of the limbs, and sensitive ataxia. According to the results of the magnetic resonance imaging (MRI) of the spinal cord, a lesion of the posterior cords on the long segment (C2-Th1) was found, which corresponds to the subacute degeneration of the spinal cord, which arose due to the deficiency of holotranscobalamin (active B12). The patient received appropriate treatment and was discharged home. Subsequently, the patient was found to have a concomitant genetic predisposition to folate cycle disorder and the development of thrombophilia. A year later, the woman again came to the neurological department. We carried out a repeated examination, evaluation of the results of the MRI of the cervical spine and other examinations in dynamics. According to the results of the literature analysis, additional markers for the diagnosis of funicular myelosis (in particular, homocysteine), the causes of hyperhomocysteinemia and its effects on the body were described. Timely detection and treatment of vitamin B12 deficiency is quite important, since in severe cases the development of spastic paraplegia is possible. Recovery of lost functions depends on the extent of spinal cord damage and the duration of the disease. If anemia is observed together with neurological symptoms, it is necessary to be especially attentive to possible funicular myelosis and to carry out appropriate diagnostic searches. And when detecting hyperhomocysteinemia, it is advisable to take into account other factors that can cause an increase in the level of homocysteine, in addition to a deficiency of vitamins B6, B12 and folic acid.